Egressos de medicina no Pará - DANTAS, Amaury Braga (2006)
From the inquiry of the egresses of medicine in Pará during the century xx, in historical time frame that understands, since the creation of the first medical school until the current days, considering the variable: amount, sort, age, schools, origin, type of exercise, academics, politics, cultural and Scientifics activities. the profiles of the egresses of first and the second half of the century; recognizing the historical dimensions and evaluating these joined profiles it is analyzed of the universities in responsible institutional context while developments entities and for the execution de educational public a philosophy to form professionals whose desired profile plays abilities and abilities capable to take care of to the society.